Larger Seed Size Shows Less Germination and Seedling Growth Decline Caused by Seed Ageing under Na2CO3 Stress in Leymus chinensis. (1st September 2019) - Ao, Yunna; Wang, Junfeng; Liu, Mengxing; Wang, Jiao; Knops, Johannes M. H.; Mu, Chunsheng
Abstract : Understanding of seed germination in sodic soils is needed to accelerate the restoration process in degraded saline‐sodic grassland. The objective of this study was to determine the influence of seed age (2 vs. 6 yr) and seed size (small vs. large) on seed germination and seedling growth in sodic grasslands. Older seeds (6 vs. 2 yr) reduced seed germination by 29%, germination potential by 36%, and the seedling vigor index by 52%. Seed size (small vs. large) reduced seed germination by 18%, germination potential by 20%, and seedling vigor by 19%. Sodic salt stress (>10 mM Na2 CO3 ) decreased germination by 64%, germination potential by 68%, and seedling vigor index by 33%. Sodic salt stress decreases in seed germination and seedling vigor increased with seed age. These findings suggest that younger and large seeds are preferable for restoration efforts in sodic soils. Thus, in regions where the soil has a high level of sodicity, we suggest that large seeds be selected and stored only for a short period of time for seeding. Core Ideas Germination of a 6‐yr‐old seed lot was reduced by seed ageing compared with a 2‐yr‐old seed lot. Light sodic salt stress increased seed germination, whereas heavy stress markedly inhibited germination and the seedling vigor index. Larger seed size partially offset reductions in germination and the seedling vigor index, especially in high sodic salt stress conditions.